Deciphering comprehensive features of tumor microenvironment controlled by chromatin regulators to predict prognosis and guide therapies in uterine corpus endometrial carcinoma - Wu, Qihui; Tian, Ruotong; Liu, Jiaxin; Ou, Chunlin; Li, Yimin; Fu, Xiaodan (Frontiers in Immunology, 2023)
Dysregulation of genome expression profiles manipulated by chromatin regulators (CRs) causes perturbation of the tumor immune microenvironment, where a comprehensive study is required to elucidate the underlying mechanism involved. Herein, we focused on uterine corpus endometrial carcinoma (UCEC) and leveraged gene expression data of CRs from TCGA-UCEC. Using weighted gene co-expression network analysis (WGCNA) and consensus clustering algorithm, the UCEC patients were classified into Cluster_L and Cluster_H. Meanwhile, WGCNA and differential gene expression analysis were used to derive TME-associated CRs. Next, a CR risk score (CRRS) consisting of 9 TME-associated CRs was constructed using univariate Cox and LASSO-Cox regression analyses. Patients with relatively lower CRRS were characterized by lower grade, relatively benign molecular subtypes and survival benefit. Based on CRRS and other clinicopathologic factors, a nomogram was developed to further predict the patients' prognosis. Further investigation suggested that patients in the low-CRRS group had abundant immune infiltration, a higher mutation burden, fewer CNVs, and a better response to immunotherapy. Finally, the low CRRS patients showed sensitive responses to 24 chemotherapeutic agents. In conclusion, a comprehensive assessment of the CRRS may allow the identification of immune activation and improve the efficacy of UCEC treatments.